2010
DOI: 10.1371/journal.pone.0011157
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F Constitutive Activation Requires JH2 Residue F595: A Pseudokinase Domain Target for Specific Inhibitors

Abstract: The JAK2 V617F mutation present in over 95% of Polycythemia Vera patients and in 50% of Essential Thrombocythemia and Primary Myelofibrosis patients renders the kinase constitutively active. In the absence of a three-dimensional structure for the full-length protein, the mechanism of activation of JAK2 V617F has remained elusive. In this study, we used functional mutagenesis to investigate the involvement of the JH2 αC helix in the constitutive activation of JAK2 V617F. We show that residue F595, located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 46 publications
11
84
1
Order By: Relevance
“…8A, the corresponding isoleucine in Jak2 JH2 is located in the N lobe, at the end of the loop connecting the b4 and b5 strands, and is a few residues away from Val 617 (48). Interestingly, it was shown that the activating V617F mutation rigidifies the JH2 aC helix through p-stacking interactions with two phenylalanines (Phe 594,595 ), confirming previous mutational studies of Jak2 V617F by Constantinescu's group (49). Yet, the mode by which the rigidified aC helix brings about JH1 activation in Jak2 V617F remains unclear.…”
Section: Discussionsupporting
confidence: 81%
“…8A, the corresponding isoleucine in Jak2 JH2 is located in the N lobe, at the end of the loop connecting the b4 and b5 strands, and is a few residues away from Val 617 (48). Interestingly, it was shown that the activating V617F mutation rigidifies the JH2 aC helix through p-stacking interactions with two phenylalanines (Phe 594,595 ), confirming previous mutational studies of Jak2 V617F by Constantinescu's group (49). Yet, the mode by which the rigidified aC helix brings about JH1 activation in Jak2 V617F remains unclear.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, a recent structure of the JAK1 pseudokinase suggests that insertion of a phenylalanine at the analogous JAK1 position (V658) induces remodeling of a highly conserved Phe residue (F575) in the N-terminal exon 12 segment (13). It has also been shown that any number of large hydrophobic residues in place of V617 can activate JAK2 (33), whereas replacement of the V617-adjacent aromatic residue F595 with a smaller aliphatic residue can reverse the increased activity conferred by V617F (34), suggesting that simple steric disruption of the packing near JAK2 V617 and exon 12 can relieve inhibition. Bulky substitutions in the pseudokinase αC-helix (e.g., JAK1 A634D, JAK3 A572V or A573V) or exon 12 deletions and insertions may also relieve autoinhibition in a similar manner to the V617F mutation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The main structural effects due to ATP binding in JH2 are observed in αC, and mutations in αC (e.g., F594A, F595A) have been shown to reverse hyperactivation of several mutations scattered throughout the JAK2 JH2-JH1 interface (18,34,35). Although in the case of V617F, which is proximal to αC, F595A might reconstitute a disrupted autoinhibitory JH2-JH1 interface, a more likely explanation for the suppressive effects of ATP binding mutations (and of F594A, F595A) is that pathogenic hyperactivation is dependent on a yet-to-be-characterized positive regulatory interaction mediated by JH2, which probably involves αC and is therefore sensitive to its conformation.…”
Section: Discussionmentioning
confidence: 99%